Advances in the Diagnosis and Treatment of Acute Kidney Injury in Cirrhosis Patients. (10th May 2017) - Lei, Lei; Li, Liangping; Zhang, Hu
Abstract : Liver cirrhosis is a common progressive and chronic clinical liver disease. Due to the strong compensation ability of the liver, no obvious symptoms develop in the early stage. However, multiple systems are involved in decompensation of the liver. Acute kidney injury (AKI) is one of the most serious complications, characterized by a sharp drop in the glomerular filtration rate (GFR); a rapid increase in Scr and BUN, as well as sodium and water storage; and a disturbance of acid-base balance. The mortality rate is high, and the prognosis is very poor. Thus, it is important to make a definite diagnosis and initiate treatment in the early stage to decrease mortality and improve the prognosis. Although diagnosing liver cirrhosis with serum creatinine has many shortcomings, a dynamic change in this marker is still the main diagnostic criterion for AKI. Identifying new markers of kidney injury with clinical value has also become an increasing focus of research. In this text, we review recent changes regarding categorization of AKI diagnostic criteria as well as new markers of AKI and treatments for cirrhosis-related AKI.